1970
DOI: 10.4314/ahs.v19i4.11
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of hospital admission respiratory disease cases attributed to exposure to SO2 and NO2 in two different sectors of Egypt

Abstract: Air Q 2.2.3 was used to predicted hospital admissions respiratory disease cases due to SO2 and NO2 exposure in two sectors of Egypt during December 2015 to November 2016. Levels were 19, 22 μg/m3 at Ain Sokhna sector and 92, 78 μg/m3 at Shoubra El-Khaima sector for SO2 and NO2, respectively. These levels were less than the Egyptian Permissible limits (125 µg/m³ in urban and 150 µg/m³ in industrial for SO2, 150 µg/m³ in urban and industrial for NO2). Results showed that relative risks were 1.0330 (1.0246 - 1.04… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The assessment was based on the attributable proportion identified as the fraction of the health effect in a given population that is attributable to a certain air pollutant [26]. Relative risks (RR) with 95% confidence interval (CI) for each 10 μg/m 3 increase in daily mean concentrations of NH 3 and H 2 S pollutants have been reported.…”
Section: Airq + Softwarementioning
confidence: 99%
See 1 more Smart Citation
“…The assessment was based on the attributable proportion identified as the fraction of the health effect in a given population that is attributable to a certain air pollutant [26]. Relative risks (RR) with 95% confidence interval (CI) for each 10 μg/m 3 increase in daily mean concentrations of NH 3 and H 2 S pollutants have been reported.…”
Section: Airq + Softwarementioning
confidence: 99%
“…These impacts should be described at the local, regional, national and global scales around the world [25]. In a previous study, an estimate of hospital admission respiratory disease due to SO 2 and NO 2 exposure was performed in Egypt by Mohammed et al [26].…”
Section: Introductionmentioning
confidence: 99%
“…He attributed higher seasonal levels to climatic conditions, topography and photochemical reaction. Mohammed et al 77 reported that the daily mean concentration SO 2 at Shoubra El-Khaima in Greater Cairo during 2016 were 60-116μg/m 3 , which lower than the Egyptian Permissible Daily (125 µg/m³ in urban and 150µg/ m³ in industrial) average limit in Annex No. 5 of the Executive Regulations of Law No.…”
Section: Resultsmentioning
confidence: 90%
“…33,76 Health impact assessment (HIA) supply decision-makers with quantitative and qualitative information about pollutants levels and its effects on humans, to help them to put policy to safe people health. 33 Mohammed et al 77 reported that a level of SO 2 was 92µg/m 3 in Greater Cairo, Egypt during 2016. Also they using Air-Q 2.2.3 model to predicted hospital admissions respiratory disease (HARD) cases due to SO 2 exposure, and they found the highest cases of HARD were 311 cases at 120-129µg/m 3 of SO 2 .…”
Section: Exposure To Pmmentioning
confidence: 99%
“…In this same context, Mohammed and colleagues have estimated the number of hospital admission for respiratory diseases attributed to SO 2 and NO 2 , in Shoubra El-Khaima and Ain Sokhna in Egypt, using Air Quality Health Impact Assessment (Air Q 2.2.3) tools. They showed important differences in the SO 2 and NO 2 hospital admission between the two studied cities [ 71 ]. For example, while Shoubra El-Khaima’s sector reported the largest risk estimates (311/234 cases attributed to exposure to SO 2 /NO 2 ), smaller estimates were found in Ain Sokhna (18/15 cases attributed to exposure to SO 2 /NO 2 ).…”
Section: Resultsmentioning
confidence: 99%